2019
DOI: 10.3892/ol.2019.11166
|View full text |Cite
|
Sign up to set email alerts
|

LINC00365‑SCGB2A1 axis inhibits the viability of breast cancer through targeting NF‑κB signaling

Abstract: Breast cancer is the most common high-grade malignancy in women. The lack of therapeutic targets has limited the treatment of breast cancer. Recently, long noncoding RNAs (lncRNAs) have been demonstrated to be dysregulated in various types of cancer. However, the specific mechanisms by which lncRNAs influence breast cancer have remained largely unclear. To bridge this research gap, the present study focused on the lncRNA LINC00365, which is expressed at a low level in breast cancer. Secretoglobin family 2A mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…LINC00501 has been identified as a prognostic factor associated with the overall survival of patients with hepatocellular carcinoma (HCC) ( 50 – 52 ). LINC00365 influences the Wnt/β-catenin signaling pathway, which modulates colorectal cancer (CRC) progression ( 53 ), and breast cancer cell viability may be regulated by the LINC00365-secretoglobin family 2A member 1 (SCGB2A1) axis, which targets NF-κB signaling ( 54 ). In GC, the expression levels of LINC00365 and SCGB2A1 are downregulated in tumor tissues, which is associated with a shorter survival time ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…LINC00501 has been identified as a prognostic factor associated with the overall survival of patients with hepatocellular carcinoma (HCC) ( 50 – 52 ). LINC00365 influences the Wnt/β-catenin signaling pathway, which modulates colorectal cancer (CRC) progression ( 53 ), and breast cancer cell viability may be regulated by the LINC00365-secretoglobin family 2A member 1 (SCGB2A1) axis, which targets NF-κB signaling ( 54 ). In GC, the expression levels of LINC00365 and SCGB2A1 are downregulated in tumor tissues, which is associated with a shorter survival time ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oppositely, LINC00365 was lower expressed in breast cancer. The up‐regulation of LINC00365 attenuated the proliferation and induced the apoptosis of breast cancer cells 14 . Therefore, the function of LINC00365 on cancers development varies with tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of LINC00365 attenuated the proliferation and induced the apoptosis of breast cancer cells. 14 Glycolysis is conductive to accelerate tumor cells proliferation and metastatic dissemination. 30,31 In this study, LINC00365 suppressed the glycolysis of H1975 cells, manifested as the reduced glucose uptake, lactate product, and cellular ATP level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 Over the past few decades, studies have shown that multiple lncRNAs are abnormally expressed in breast cancer. 18–20 Therefore, it is important for the identification of breast cancer clinical treatment to dissect the role of lncRNAs in breast cancer progression. In our study, we found that the expression levels of lncRNA SNHG8 were elevated in breast cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%